A generalised framework to support field and in–class collaborative learning. (23rd January 2015) - Ahmad, Madiha Shafaat; Pinkwart, Niels
Mobile technologies have proven their value in field learning. Meanwhile, classroom technologies such as multi–touch interactive tables are gaining attention as well. With shareable interfaces and larger displays, multi–touch tables enable multiple students to interact and collaborate more flexibly. Thus, today's technology provides different means to facilitate learning both indoor and outdoor, in the form of specialised devices; yet an integrative view is missing in the literature so far. The goal of this paper is to propose a generic framework, capable of connecting different kinds of devices, such that the most suited device can be employed for each specific learning activity. Based on this framework, a pilot system has been developed that allows students to collect data through tablets on a field trip and share it with other peers via Bluetooth. Learners could also take part in a quiz, sent by the teacher to their mobile devices, and send their results back to the teacher through Bluetooth.